The quest for a killer KPI : how radically simplifying performance metrics helped one company align employee behavior with organizational goals, make smarter investments in the business, and foster a culture of learning and cooperation - Morgenshtern, Omri; Rosenstein, Robert; Allen, Peter L. (MIT Sloan Management Review, 2022)
This is the story of how Agoda, a subsidiary of the Booking Holdings online travel group, made its way to a single "KPI + constraint" model that helps run a good bit of the business. It took some trial and error to get there; the KPIs that were developed and tested along the way promoted both positive and counterproductive behaviors and outcomes. But the business found its guiding principles, implemented them, improved performance, and fostered learning and cooperation in the process.